DEVELOPMENT AND IN VITRO EVALUATION OF PHYTOSOMES OF NARINGIN - JEEVANA JYOTHI B; MARY RAGALATHA P (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Phytosomes are novel herbal formulations meant for design of poorly soluble flavonoids of therapeutic potential. Naringin is a flavanone with poor oral absorption and bioavailability but possess antioxidant, anti-inflammatory, antiapoptotic, anti-ulcer, antiosteoporotic, and anticarcinogenic effects. Hence, the objective of the present work is the development of phytosomes of naringin to enhance its dissolution so that its therapeutic effects can be exploited. Materials and Methods: Phytosomes containing 350 mg of naringin were prepared by antisolvent precipitation method and rotary evaporation method using soya lecithin as main polymer. The prepared phytosomes were evaluated by entrapment efficiency, in vitro drug release studies, and drug-excipient interaction studies. Results: Phytosomes made by rotary evaporation method evidenced higher dissolution values than phytosomes made by antisolvent precipitation. Formulation F7 containing 350 mg of naringin and 1400 mg of soya lecithin revealed the highest percentage release of 84.5±0.39% in 60 min and 99.7±0.24% in 120 min. The percentage of drug entrapment efficiency values was satisfactory. Fourier-transform infrared spectroscopy spectra of pure naringin and naringin phytosomes revealed no interaction between the drug and polymers used for preparation. Conclusion: Naringin phytosomes are produced successfully by the rotary evaporation method. Phytosomes made with 350 mg of naringin and 1400 mg of soya lecithin by rotary evaporation method are spherical with a rough outer surface and optimum release characteristics of 84.5±0.39 in 60 min to possess optimum bioavailability and 99.7% in 120 min.